Pendampingan BUMDes Dalam Pengelolaan PAMSIMAS serta Sosialisasi Pola Hidup Bersih dan Sehat di Desa Gadingan - Prasetya, Rendra Chriestedy; Sampurna, Hadi; Suryadharma, Bertung; Hernawati, Sri; Apriyono, Dwi Kartika (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2024)
Gadingan Village is located on the coast of Jangkar District, Situbondo Regency. Some residents have difficulty accessing clean water. In 2020, Gadingan Village received PAMSIMAS grants including drilling for water sources, deep water pumps, and reservoirs. Currently, these facilities have not been fully utilized because the management agency has not yet been formed. The Gadingan Village Government encourages BUMDes as PAMSIMAS managers, but BUMDes does not yet have knowledge of network management and planning. People who use water do not believe in the quality of the water and the quantity of the water. The problem solving method used is the socialization of PHBS and PAMSIMAS to the community, as well as BUMDes assistance for PAMSIMAS management and PHBS awareness. The results obtained are increased public awareness in the use of clean water and the provision of sanitation and hygiene facilities.